MAKING OF WEB-BASED INFORMATION MEDIA FOR CULINARY MEDAN AS A MEANS OF PROMOTION USING UCD (USER CENTER DESIGN) METHOD - Ridho Teguh Sanjaya; Marnis Nasution; Syaiful Zuhri Harahap (INFOKUM, 2021)
Culinary is a part of life that is closely related to daily food consumption. Culinary is a lifestyle that cannot be separated from everyday life. Because everyone needs food that is needed daily. Starting from simple food to high-class and luxurious food Promotion is a communication technique that is used or delivered by using media such as press, television, radio, signboards, posters, and others whose aim is to attract consumer interest in the production of a product. company. Promotion as a medium to bridge the interests of producers with consumers. UCD (User-Centered Design) is a new paradigm in the development of web-based systems. User-centered design (User-Centered Design = UCD) is a term used to describe a design philosophy. The concept of UCD is that the user is at the center of the system development process, and the objectives of the nature, context, and environment of the system are all based on the user experience. PHP is a server-side programming language that is widely used today, especially for creating dynamic websites. For certain things in web development, the PHP programming language is needed, for example to process data sent by web visitors.